AN APPROACH FOR HYPERSURFACE FAMILY WITH COMMON GEODESIC CURVE IN THE 4D GALILEAN SPACE G4 - Yoon, Dae Won; Yuzbasi, Zuhal Kucukarslan (Korean Soc Mathematical Education, 2018)
In the present study, we derive the problem of constructing a hypersurface family from a given isogeodesic curve in the 4D Galilean space G(4). We obtain the hypersurface as a linear combination of the Frenet frame in G(4) and examine the necessary and sufficient conditions for the curve as a geodesic curve. Finally, some examples related to our method are given for the sake of clarity.
Keywords: Galilean space; hypersurface; geodesic